Project implementation plan: Piloting and scaling of low emission development options in large scale dairy farms in China - Dong, Hongmin (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This project implementation plan was presented by Hongmin Dong (CAAS) at the Kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" on September 28th, 2020.